2021
DOI: 10.1002/jso.26454
|View full text |Cite
|
Sign up to set email alerts
|

Log ODDS (LODDS) of positive lymph nodes as a predictor of overall survival in squamous cell carcinoma of the penis

Abstract: Objective: To evaluate the role of logarithmic ODDS (LODDS) in the number of positive lymph nodes and the number of negative lymph nodes as a prognostic metric in the squamous cell carcinoma (SCC) penis.Methods: Data were retrospectively collected from 96 cases of SCC penis that underwent bilateral groin dissection between 2010 and 2015 at our institute.Lymph node density (LND) and LODDS were calculated for all the patients and classified according to American Joint Committee on Cancer (AJCC) pN staging.Thresh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…A retrospective study had shown that LODDS was a superior predictive indicator for disease-free survival compared to pN and LNR in patients with rectal cancer [ 16 ]. Similar results and conclusions can be found in various studies with different cancers including lung squamous cell carcinoma [ 17 ], squamous cell carcinoma of the penis [ 18 ], colon cancer [ 19 ], endometrial carcinosarcoma [ 20 ], etc. For bladder cancer, Jin et al assessed the predictive capacity of pN, LNR, and LODDS in patients with muscle-invasive urothelial carcinoma of bladder cancer [ 12 ].…”
Section: Discussionsupporting
confidence: 88%
“…A retrospective study had shown that LODDS was a superior predictive indicator for disease-free survival compared to pN and LNR in patients with rectal cancer [ 16 ]. Similar results and conclusions can be found in various studies with different cancers including lung squamous cell carcinoma [ 17 ], squamous cell carcinoma of the penis [ 18 ], colon cancer [ 19 ], endometrial carcinosarcoma [ 20 ], etc. For bladder cancer, Jin et al assessed the predictive capacity of pN, LNR, and LODDS in patients with muscle-invasive urothelial carcinoma of bladder cancer [ 12 ].…”
Section: Discussionsupporting
confidence: 88%
“…LODDS has also been found to be better for several tumors. In penile cancer ( 38 ), LODDS (log-likelihood = 3832 vs. 3798; p < 0.001) had better prognostic performance than pN and better discriminability than lymph node density (AIC = 3902 vs. 3928).…”
Section: Discussionmentioning
confidence: 96%
“…indicates that LODDS is an independent predictor of OS in the squamous cell carcinoma of the penis. It has a superior prognostic significance than lymph node density classification and AJCC N stage systems ( 31 ). Similarly, Yang et al.…”
Section: Discussionmentioning
confidence: 99%